Pengembangan Modul Ajar Matematika Berbasis Problem Based Learning pada Materi Rasio untuk Memfasilitasi Kemampuan Pemecahan Masalah Matematis Fase D Kelas VII SMP - Mardiah, Ainul; Saragih, Sehatta; Murni, Atma (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study is essential, given the lack of adequate learning materials for students in developing Mathematical Problem Solving Skills (KPMM) and the skills needed for more optimal results. The research involved 39 students from class VIII.7 at SMP Negeri 8 Pekanbaru during the odd semester of the 2023/2024 academic year. The research methods included a one-to-one test subject consisting of three high-performing students, a small group test subject involving six students with heterogeneous abilities, and a large group test subject also based on heterogeneous abilities. A 4-D approach consisting of define, design, development, and disseminate was used in material development. Data was collected through observation, interviews, and questionnaires. Interviews were conducted to identify the main problems that form the basis for module development, observations to assess the learning process, and questionnaires to obtain feedback from validators and students about the developed product. The study results showed that the learning module designed according to the independent curriculum with ratio content for seventh-grade students in phase D and a problem-based learning model is proven to be valid and practical.